Hormones of hypothalamic-pituitary-gonadal axis in alcohol withdrawal and their relationships with aggression - Özsoy, Saliha; Eşel, Ertuğrul (Journal of Dependence, 2007)
Objective: Alcohol is known to have some influences on hypothalamic-pituitary-gonadal (HPG) axis activity. Some changes in HPG axis hormones may be related to aggression in alcoholic patients. The study aims to investigate the relationship between HPG axis alterations and aggression level in alcoholic patients during early and late alcohol withdrawal. Method: Alcoholdependentmaleswithoutdepression (n=28) and healthy control male subjects (n=19) were rated with neuropsychological tests measuring immediate and life-long aggression. The patients were divided into two subgroups according to their (high or low) level of aggression in Brown-Goodwin Aggression scale. Serum levels of total testosterone, luteinizing hormone (LH) and follicle-stimulating hormone (FSH) were measured on the first and 28th days of withdrawal periods in alcohol dependents and once in healthy controls. Results: The study revealed increased total testosterone level in early withdrawal and increased LH level during both early and late withdrawal periods in all alcoholic patients. When the patients were assessed in two separate groups as high- and low-aggressives, it was found that LH level was high during early and late withdrawal in both groups compared to controls. While testosterone level was high in low-aggression group only in early withdrawal, it was increased in high-aggression group during both early and late withdrawal periods. Conclusion: Alterations of testosterone level during alcohol withdrawal may be associated not only with chronic alcohol use per se but also with aggressivity that is present in some of alcoholic patients.